A CMOS mixed-signal interface with a RF transmitter for a micromachined soil moisture sensor - Morais, Raul (2003)
This paper describes a CMOS mixed-signal interface with a RF transmitter. This die is assembled in a Multi-Chip-Module (MCM) micro-system together with the micromachined soil moisture sensor to achieve a cost effective solution with accurate and reliable measurements for soil moisture in agriculture. The soil moisture probe, based on Dual-Probe Heat-Pulse (DPHP) method, is fabricated in bulkmicromachining technology. The DPHP method is based on the measurement of the maximum temperature rise at some distance from the heater, after applying a heat-pulse. The measurement of the temperature rise is obtained by subtracting soil temperature from the probe temperature. The mixed-signal interface is based on a pre-amplification stage and first-order sigma-delta modulator. The bit-stream output of the modulator is then applied to a counter as a first order decimation filter thus providing a 12-bit readout sample. Prior to transmission, data is encoded as a pulse width modulated (PWM) signal and then transmitted by means of an amplitude shift-keying (ASK) modulation. The transmitter features a VCO phase locked to the quartz crystal reference of 13.56 MHz to achieve a carrier frequency of 433.92 MHz. A RF power amplifier based on class E topology was chosen. The CMOS mixed-signal interface with a RF transmitter has been implemented in a single-chip using a standard CMOS process (AMI 0.7 µm, n-well, 2 metals and 1poly).